Call to Duty: Just-in-Time Scheduling in a Restaurant Chain - Kamalahmadi, Masoud; Yu, Qiuping; Zhou, Yong-Pin (Management Science, 2021)
Just-in-time scheduling has become ubiquitous in the service industries. Although effective in reducing staffing level, hence labor cost, the potential impact of just-in-time scheduling on workers’ productivity and the firm’s revenue is not well understood. Using a data set of 1,444,044 transactions from 25 stores of a full-service casual dining restaurant chain in the United States, we study how just-in-time scheduling impacts worker productivity. We consider two types of just-in-time schedules: (1) short-notice schedules that are assigned to servers shortly before the day of service (mostly two days in our data) and (2) real-time schedules that are assigned to servers on the day of service. We show that short-notice schedules do not harm server productivity overall, but real-time schedules do by 4.4%. Our analysis indicates this may be because servers reduce their up-selling and cross-selling efforts when working on real-time schedules. We then propose an analytical scheduling model that accounts for both the value of staffing flexibility created through just-in-time scheduling and its impact on server productivity to inform the firm how to use just-in-time scheduling to improve profitability. Through a case study, we demonstrate that with the 4.4% productivity loss during the real-time schedules, the managers should shift from the heavy use of real-time scheduling toward scheduling more servers with longer advance notice. Such a shift not only provides more predictable work schedules for the workers but can also improve restaurants’ expected profit by up to 1%, a significant number for the low-margin restaurant industry. This paper was accepted by Vishal Gaur, operations management.